2009
DOI: 10.1345/aph.1l537
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect of Ginkgo biloba on Voriconazole Pharmacokinetics in Chinese Volunteers Identified as CYP2C19 Poor and Extensive Metabolizers

Abstract: The results suggest that 12 days of treatment with Ginkgo biloba did not significantly alter the single-dose pharmacokinetics of voriconazole in either CYP2C19 extensive or poor metabolizers. Therefore, the pharmacokinetic interactions between voriconazole and Ginkgo biloba may have limited clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 23 publications
2
20
0
2
Order By: Relevance
“…The impact of CYP2C19 genetic variants on voriconazole pharmacokinetics has been confirmed and characterized in a number studies in adult healthy volunteers (Table 2) [7,8,7680]. Pharmacokinetic parameters including half-life (t 1/2 ) and AUC are significantly increased in CYP2C19 PM compared to CYP2C19 EM receiving oral voriconazole.…”
Section: Voriconazole Pharmacokinetics and Cyp2c19 Polymorphismsmentioning
confidence: 88%
“…The impact of CYP2C19 genetic variants on voriconazole pharmacokinetics has been confirmed and characterized in a number studies in adult healthy volunteers (Table 2) [7,8,7680]. Pharmacokinetic parameters including half-life (t 1/2 ) and AUC are significantly increased in CYP2C19 PM compared to CYP2C19 EM receiving oral voriconazole.…”
Section: Voriconazole Pharmacokinetics and Cyp2c19 Polymorphismsmentioning
confidence: 88%
“…At 0.25 h after administration, GK was detected at the highest concentration in all of these tissues, while it was generally cleared from all of these tissues at 4 h. Besides, liver showed significantly higher levels of GK exposure, followed by kidney, heart, and spleen in that order, which may be attributed to the blood flow in these organs. Recently, ginkgo has been reported to have multiple interaction with other drugs base on the influence of CYP2C19 [30], the accumulation of GK on liver indicated that it was also important to concern the interaction between GK and co-administrated drugs. In addition, the concentration of GK in the brain was extremely low, suggesting that GK was difficult to cross the blood-brain barrier of normal rats, this may due to the p-gp efflux accompanied by the para-cellular pathway for passive diffusion [31].…”
Section: Tissue Distribution Studymentioning
confidence: 99%
“…Ginkgo biloba is generally considered safe and well tolerated in the general population, however, it may induce drug interactions [22]. Human studies have found no significant effect for ginkgo biloba on cytochromes 2B6, 2C19 or 2C9 and a study of elderly volunteers found no significant effect on CYP3A4 although the herb does appear to induce CYP3A in young volunteers [37][38][39][40][41]. Several case reports have suggested a link between ginkgo biloba ingestion and haemorrhage, however, the reliability of these cases is questionable as several clinical studies found no significant effects on bleeding with ginkgo ingestion [27][28][29][30][31][32][33][34][35][36].…”
Section: The Quality Control Regulation Of Complementary Medicine Promentioning
confidence: 99%